ANALISIS KOMPARATIF PRESTASI BELAJAR KELOMPOK PENERIMA KIP-K DAN REGULER PADA MAHASISWA PENDIDIKAN EKONOMI FKIP UNS - Nur Rohmah; Sudarno; Feri Setyowibowo (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2024)
The purpose of this study was to gain an understanding of the differences between the learning achievement of groups that received KIP-K and those who did not and to identify the effect of interest in learning, achievement motivation, intelligence, family, and environment on student achievement. This study is a comparative study using quantitative methods involving 286 students as a population and 166 students as a sample from the FKIP UNS Economics Education study program. The purposive sampling method was used to select the sample. A Likert scale questionnaire was used as a data collection tool, and chi-square analysis was used to analyze the data. The research findings show that there is a significant difference in learning achievement between KIP-K recipients and regular groups with Sig. (2-tailed) of 0.000 < 0.05. Learning interest has a significant effect on regular group learning achievement with Asymptote scores. Sig (2-sided) of 0.022 < 0.05. Meanwhile, achievement motivation had a significant effect on the learning achievement of the KIP-K recipient group with an Asymptote value. Sig (2-sided) of 0.019 < 0.05. Meanwhile, intelligence, family, and environmental factors did not significantly affect the learning achievement of the KIP-K and regular recipient groups, as seen from the Asymp scores. Sig (2-sided) > 0.05.